If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8r-36=-6(1+8r)
We move all terms to the left:
-8r-36-(-6(1+8r))=0
We add all the numbers together, and all the variables
-8r-(-6(8r+1))-36=0
We calculate terms in parentheses: -(-6(8r+1)), so:We get rid of parentheses
-6(8r+1)
We multiply parentheses
-48r-6
Back to the equation:
-(-48r-6)
-8r+48r+6-36=0
We add all the numbers together, and all the variables
40r-30=0
We move all terms containing r to the left, all other terms to the right
40r=30
r=30/40
r=3/4
| 200m-75m+62075=66625-200m | | -15+8a=20+3a | | 3x-1-4x+21=33 | | 3.2-10=2.4x+6 | | x+53+65+70=180 | | -4(x-11)=-20 | | 8-k=13 | | 11+3/4x=-13 | | 11+3/4x=-12 | | 1/4x+5=20 | | 1/3a+-12=4/3a+6 | | -5(2x-4)+6=6x+5+3x+8 | | 11−m=51−6m | | 5.4+x=7.5 | | 22=1+8a+5 | | X+x/3=2 | | 12-3g=18 | | -33+4x=3 | | 3v+24=6v | | x2−12=−14 | | 4x+-8=-x3+13 | | -6k-6=7(3k+3) | | 7(x-9)-8=27 | | -4=2r+4r | | 2-x=-x+7 | | 8/5(4.5-6)=-1/5(2z+3) | | q/2− 1=1.5 | | 8t-2=10t | | 6y+11=2y+47 | | 4x+2x+2=2(3x+2) | | 9(x−3)+3x=7x+43 | | 30=-5(2n+8) |